Conserved UBE3A subcellular distribution between human and mice is facilitated by non-homologous isoforms. (2nd September 2020) - Zampeta, F Isabella; Sonzogni, Monica; Niggl, Eva; Lendemeijer, Bas; Smeenk, Hilde; de Vrij, Femke M S; Kushner, Steven A; Distel, Ben; Elgersma, Ype
Abstract: The human UBE3A gene, which is essential for normal neurodevelopment, encodes three Ubiquitin E3 ligase A (UBE3A) protein isoforms. However, the subcellular localization and relative abundance of these human UBE3A isoforms are unknown. We found, as previously reported in mice, that UBE3A is predominantly nuclear in human neurons. However, this conserved subcellular distribution is achieved by strikingly distinct cis- acting mechanisms. A single amino-acid deletion in the N-terminus of human hUBE3A-Iso3, which is homologous to cytosolic mouse mUBE3A-Iso2, results in its translocation to the nucleus. This singe amino-acid deletion is shared with apes and Old World monkeys and was preceded by the appearance of the cytosolic hUBE3A-Iso2 isoform. This hUBE3A-Iso2 isoform arose after the lineage of New World monkeys and Old World monkeys separated from the Tarsiers ( Tarsiidae ). Due to the loss of a single nucleotide in a non-coding exon, this exon became in frame with the remainder of the UBE3A protein. RNA-seq analysis of human brain samples showed that the human UBE3A isoforms arise by alternative splicing. Consistent with the predominant nuclear enrichment of UBE3A in human neurons, the two nuclear-localized isoforms, hUBE3A-Iso1 and -Iso3, are the most abundantly expressed isoforms of UBE3A, while hUBE3A-Iso2 maintains a small pool of cytosolic UBE3A. Our findings provide new insight into UBE3A localization and evolution and may have important implications for gene therapy approaches in Angelman syndrome.